P Pengaruh Partisipasi Anggaran, Kejelasan Anggaran, Komitmen Organisasi Terhadap Senjangan Anggaran - Siswiraningtyas, Anggraeni Nur; Indrawati Yuhertiana (STEKOM PRESS, 2021)
This study aims to examine and analyze the effect of budgetary participation, clarity of budget targets, organizational commitment to budgetary slack. This research uses quantitative research using primary data. The primary data is a questionnaire that distributed to respondents. This research used PLS-SEM with the help of SmartPLS version 3.0 for windows software to data analysis. This results prove that the variables of budgetary participation, clarity of targets, and organizational commitment have an influence on budgetary slack.